Bacterial communities in the phylloplane of Prunus species. (16th December 2014) - Jo, Yeonhwa; Cho, Jin Kyong; Choi, Hoseong; Chu, Hyosub; Lian, Sen; Cho, Won Kyong
<x xml:space="preserve">Abstract</x> Bacterial populations in the phylloplane of four different Prunus species were investigated by 16 S rRNA pyrosequencing. Bioinformatic analysis identified an average of 510 operational taxonomic units belonging to 159 genera in 76 families. The two genera, Sphingomonas and Methylobacterium, were dominant in the phylloplane of four Prunus species. Twenty three genera were commonly identified in the four Prunus species, indicating a high level of bacterial diversity dependent on the plant species. Our study based on 16 S rRNA sequencing reveals the complexity of bacterial diversity in the phylloplane of Prunus species in detail.